Perception and practices of solid waste management among adults in households and commercial establishments of villages under a sub centre, Bangalore urban district: a mixed methods study - Kona, Chandralekha; Agrawal, Twinkle; Fathima, Farah Naaz; Mathias, Sitarah; Gowda, Hemanth; Makri, Helena; Devraj, Srilakshmi (International Journal Of Community Medicine And Public Health, 2023)
Introduction: Solid waste management in rural areas is laced with many challenges which involve multiple stakeholders. Objective was to explore the perspectives and practices of adults regarding solid waste management in households and commercial establishments of villages under a sub-centre, Bangalore Urban district. Methods: A mixed method study (Quantitative and Qualitative) was conducted at a sub-centre area which caters to 10 villages of Bangalore urban district, Karnataka over a period of two months (January 2019 to February 2019). Quantitative data was collected from 200 adult participants while for the qualitative part a total of 2 FGDs and 10 IDIs were conducted. Results: Mean age of the participants was 40.2±14.7 years and majority (83%) of them were female. Mean perception score of the participants was 6.7±2.4 out of a total of 14. The most commonly reported disposal methods were burning (51.5%) followed by dumping in open spaces (48%). Majority (96.5%) were willing to keep the streets clean, 53% were willing to segregate waste or compost (49%). Although the participants were aware of harmful effects of improper management of solid waste on environment and health, good practices were inadequate. Scarcity of appropriate dumping sites, lack of transportation facilities of waste to the dumping site and non-co-operation among the residents emerged as the barriers in solid waste management. Conclusions: Lack of land availability and social consciousness among the villagers played a major role in solid waste management. Addressing this issue demands a intersectoral co-ordination with interventions directed at empowering the villagers and local bodies and enhancing their involvement in proper waste management.